PENGEMBANGAN SEKOLAH INKLUSIF DENGAN MENGGUNAKAN INSTRUMEN INDEKS FOR INCLUSION - JAUHARI, MUHAMMAD NURROHMAN (Fakultas Pedagogi dan Psikologi Universitas PGRI Adi Buana Surabaya, 2017)
Inclusive education is to provide education system that provides opportunities for all learners who have the disorder and have intelligence and special talents to participate in education or learning in an educational setting together with the learners in general. The problems that occurred in the implementation of inclusive education include the acceptance of students with special needs; identification and assessment; lack of understanding of teachers to the school curriculum inclusive; fields of energy, duty and authority; classroom management system; learning process; Facilities and infrastructure; the understanding of the school and the community about inclusive schools and children with special needs. To address the issue of implementation of inclusive schools using instruments Index for Inclusion as an effort to develop a suitable school with inclusive value in terms of three dimensions, namely: (1) the dimensions of culture (creating inclusive cultures), (2) the dimensions of policy (producing inclusive policies) and (3) the dimensions of practice (evolving inclusive practices). Each dimension is divided into two sections. namely: cultural dimension consists to build a community (community building), and build inclusive values ​​(establishing inclusive values). Dimension policy consists of the development section the place for all (developing setting for all) and implement support for diversity (organizing support for diversity). While the dimensions of the practice consist of sections to learn and play together (orchestrating play and learning) and mobilization of resources (Mobilizing resources.)